2013
DOI: 10.11604/pamj.2013.15.1.2228
|View full text |Cite
|
Sign up to set email alerts
|

Résultats fonctionnels des lésions des tendons fléchisseurs de la main: à propos de 90 cas

Abstract: Les auteurs rapportent une série de 90 patients, présentant une section tendineuse des fléchisseurs de la main, et suivis avec un recul moyen de 8 mois (min: 2 mois; max: 13 mois). La lésion était localisée dans 12% des cas en zone I, 46% des cas en zone II, 2% en zone III et 25% des cas en zone IV et V. Pour le pouce (13 patients), 10 cas en zone T2 et 3 cas en zone T3. La technique opératoire utilisée était les sutures tendineuses en cadre de Kessler modifié, associée à un surjet épitendineux. Nous avons obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
4
20
1
1
Order By: Relevance
“…Results of the present study showed that 23.0% of subjects exhibited psychiatric disorders. This finding is consistent with the results of Adedeji et al [ 19 ]. Women suffer higher levels of depression and generalized anxiety compared with men but have lower levels of difficulties in the category of other psychiatric disorders ( p < 0.001).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Results of the present study showed that 23.0% of subjects exhibited psychiatric disorders. This finding is consistent with the results of Adedeji et al [ 19 ]. Women suffer higher levels of depression and generalized anxiety compared with men but have lower levels of difficulties in the category of other psychiatric disorders ( p < 0.001).…”
Section: Discussionsupporting
confidence: 94%
“…The mean age for the incidence of corrosive injuries is 44.6 ± 20 years, and 71.2% of subjects were young adults. Current findings are consistent with findings obtained in other countries [ 19 21 ]. Typically, young adults that constitute this group are in a period of life when they are most creative and productive in terms of overall working capacities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…6 The relationship between ART duration and BMI is inconsistent. 6,35,36 In a longitudinal study, weight gain was observed in a short ART duration (24 weeks) that was followed by weight loss in people treated with stavudine-based ART and maintained weight gain in people treated with tenofovir after 144 weeks. 37 Therefore, according to Crum-Cianflone et al (2008), 6 the differences in ART duration may account for variations in this relationship between ART duration and BMI.…”
Section: Discussionmentioning
confidence: 99%